Digital radiographic evaluation of optical density of porcelains used for fabrication of inlay/onlay prosthesis - Castilho, Julio Cezar de Melo [UNESP]; Takeshita, Wilton Mitsunari [UNESP]; Dos Santos, Luis Roque de Araújo [UNESP]; De Moraes, Luiz Cesar [UNESP]; Medici Filho, Edmundo [UNESP]; De Moraes, Mari Eli Leonelli [UNESP] (FapUNIFESP (SciELO), 2006)
The purpose of this article was to compare the mean value of optical density of four porcelains commonly used for fabrication of inlay/ onlay prostheses using direct digital radiograph. The sample consisted of 20 2-mm thick porcelain specimens (measured by digital pachymeter): Empress (Ivoclair), Simbios (Degussa), Vita Omega 900 and Vitadur Alpha (Vita Zahnfabrik). The values of optical density of the specimens were expressed in millimeters aluminum equivalent (mm eq Al). The samples were X-rayed using two charge coupled devices (CCD) - RVG (Trophy) - Visualix (Gendex) and a phosphor plate system - Digora (Soredex). The optical density reading was performed with Image Tool 1.28 in a total of 110 measurements. Statistical analysis showed that there were statistically significant differences in all materials studied (p < 0.05) regardless of the radiographic system used. The highest optical density value was found for Omega 900 (1.8988 mmeqAl - Visualix - Gendex) and the lowest for Vitadur Alpha (0.8647 - Visualix - Gendex). Thus, the material presenting the highest degree of optical density was Omega 900, Empress and Simbios presented intermediate optical density values, Vitadur Alpha presented the lowest value, and the optical density of porcelains was not influenced by the digital radiography systems.
Keywords: Dental porcelain; Digital radiography